Types and areas of collective participation in the Arbaeen walk - S. Ramezani Tamijani (Taḥqīqāt-i Farhangī-i Īrān, 2020)
Studying the types of participation in Ashura rituals in Shi’a’s societies has great importance due to intense intermixture that has been established with collective conscience of the followers of this religion. Meanwhile, the study of the Arbaeen walking ritual, which has shown wonderful changes in recent years and become a special and multifaceted socio-cultural phenomenon, has increased importance. Therefore, this article has considered the description and analysis of areas and types of collective participation in Arbaeen Walk phenomenon. 17 semi-structured interviews are conducted with Iranian servants and Managers of different Mukeb as the group with most level and scope of the conflict with this phenomenon in comparing with other participants. Analyzing the content of the interviews by using a combination of thematic analysis and ideal type making methods, after three coding steps, led us to 10 themes in relation to the areas of participation and 12 themes in relation to the type of participation. And finally, it was concluded that we are facing a unique kind of participation in the Arbaeen Walking.